About the Hippocratic Oath - Domínguez, Pedro (1996)
The origins of Western medicine are located on the island of Cos, small Greek territory to neighboring Asia Minor. It ruled out any medicine that divine influence in explaining the disease and its causes rather sought natural disorders developed. His concepts were developed in different works written in the V and IV centuries BC; these works had considerable influence in Greece and the ancient world. The most famous physician of this school was Hippocrates, who was born on the island mentioned in 460 BC, but from whom there is little reliable information, much of which is based on a biography written by Soranus. Greek physician who lived in the second century after Christ. Hippocrates lived no doubt it is directly mentioned by Plato in his Dialogues PROTAG pray and Phaedrus and Aristotle's Politics.